Pengaruh Work Family Conflict dan Stress Kerja terhadap Kinerja Pegawai pada Dinas Kesehatan Kabupaten Tabanan - Dewi, Bulan Cantika; Suartina, I Wayan; Mashyuni, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study was to determine the partial and simultaneous effect between the Effect of Work Family Conflict and Work Stress on Employee Performance at the Tabanan District Health Office. This study was conducted at the Tabanan Regency Health Office with the number of samples used were all employees of the Tabanan Regency Health Office as many as 70 people with a sampling method using the saturated sample method. Data collection methods are carried out by observation, interviews, and questionnaires. The data analysis technique used in this study used multiple linear regression analysis, determination coefficient test, t test and F test. The results found in this study are 1) Work family conflict has a positive and significant effect on employee performance at the Tabanan District Health Office 2) Work stress has a negative and significant effect on employee performance at the Tabanan District Health Office. 3) Work family conflict and work stress simultaneously have a positive and significant effect on employee performance at the Tabanan District Health Office. Suggestions that can be given by researchers are employees of the Tabanan Regency Health Office to be able to work more professionally in adjusting behavior while working in the office by not mixing bad habits that affect the way of working.